Outcomes from the International Survey Informing Greater Insights in Opioid Dependence Treatment (INSIGHT) project*. (December 2014) - Abagiu, Adrian Octavian; Cavar, Zrinka; Dannon, Pinhas; George, Philip; Habrat, Boguslaw; Mahomedy, Zubeida; Popov, Petr; Sarasvita, Riza; Utami, Diah Setia; Kastelic, Andrej
Abstract Aims: The International Survey Informing Greater Insights in Opioid Dependence Treatment (INSIGHT) study evaluated the implementation of opioid dependence treatment across different countries to assess treatment delivery, quality of care and outcomes. Methods: A questionnaire-based survey was used to gather data in nine countries across Central and Eastern Europe, South Africa and South-East Asia, from patients with opioid dependence receiving medication-assisted treatment (MAT), healthcare professionals (HCPs) who cared for opioid-dependent patients and opioid users not receiving MAT. Findings: There was substantial variation between countries, but overall results suggest that several aspects of MAT can be improved, such as access to treatment (conditions to start or remain in treatment), quality of care (availability/awareness of treatment options and appropriate medication dosing) and treatment outcomes (on-top use, misuse and diversion). Conclusions: This analysis highlights key priorities that should improve the quality of opioid dependence care and access to treatment. These priorities include: acknowledging opioid dependence as a chronic medical condition requiring long-term treatment; recognition by policymakers of the cost-effectiveness of treatment; making available, to those who want them, psychosocial interventions and educating HCPs to prescribe the safest, least divertible forms of medications available at optimal doses in order to reduce opioid use, misuse and diversion.